Geographic Distribution and Estimating the Childhood Cancer Incidence in Iran: Three-Source Capture-Recapture Analysis on National Registries Data - Mahmoud Khodadost; Arash Fattahi; Nasrin Hoseiny Nejad; Azad Shokri; Hamed Fattahi; Fatemeh Sarvi; Alireza Mosavi-Jarrahi (Tehran University of Medical Sciences, 2022)
Background: Cancers seldom happen in childhood age and awareness of accurate cancer incidence is essential in order to preventive programs. This study aimed to estimate the childhood cancer incidence in Iran using the three-source capture -recapture method. Methods: Total new cases of childhood cancer reported by three national data sources of MAHAK charity database, pathology reports and clinical records in Iran were enrolled in this study. The common cases among three sources were determined using data linkage method. The childhood incidence rate per 1 million populations was estimated based on three-source capture-recapture method. We used BIC, G2 and AIC statistics to select the best-fit model. Arch GIS was used to determine geographic distribution. Results: Overall, 2567 childhood cancer was included by three sources of registries. The total estimated number of childhood cancer was 5388 (95% CI: 4742.15-6228,14). The higher estimated incidence rate was Leukemia, Lymphoma by 94.91 and 24.80 per 1 million populations and the lower incidence was liver and retinoblastoma with 2.35 and 7.01 per 1 million populations. Provinces of Ardabil and Kohgiluyeh with an incidence rate of 420.01 and 404.61 per 1 million populations had a higher incidence rate and Mazandaran and Ilam with an incidence rate of 60.87 and 66.88 per 1 million populations had the lowest incidence. The overall completeness of the childhood cancer registry based on three-source was 48%. Conclusion: The low-quality childhood cancer registration system highlights the needs for urgent screening programs for early detection in the high prevalent area in Iran.